Khamir Pada Produk Pangan Peternakan Telur dan Potensi Khamir Sebagai Agen Fermentasi - Soerya, Fatima Aulia; Pratama, Andry; Putranto, Wendry Setiyadi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The adaptive nature of yeast growth to normal temperatures makes it easy to live in foodstuffs, such as eggs. Yeast as a fermentation agent has long been used for its ability to extend shelf life and improve product quality. The purpose of this article paper is to analyze and collect studies on yeast in eggs and its potential as a fermentation agent. Based on the studies analyzed and collected several yeasts from eggs namely Candida, Rhodotorula, Thricosporon, Hypopichia, and Torulaspora. It was found that the potential of yeast as a fermentation agent is useful for the field of food to the field of fuel renewal technology. Its properties that convert sugar into alcohol and CO2 can improve the characteristics of food products, while also producing fuel renewal in the form of bioethanol from coconut water.